Bangladesh Rural Advancement Committee auditors' report and accounts for the year ended December 31, 1989 - BRAC (© BRAC, 2016)
This Financial Statement prepared by Acnabin Co. Chartered Accountants, 74, Bijoy Nagar (2nd floor), Segunbagicha, Dhaka-1000.